Neues Leistungsstörungs- und Kaufrecht. Eine Zwischenbilanz. Vortrag, gehalten vor der Juristischen Gesellschaft zu Berlin am 14. Januar 2004 - Lorenz, Stephan (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2004)
[New Default and Purchasing Law. An Interim Review]The written version of a lecture given to the Berlin Legal Society. The author makes an initial assessment of the new Default and Purchasing Act two years after the Law of Obligations Modernisation Act came into force. Both the pseudo-problems and the real problems of this area are illustrated here, as are individual questions of the conformity to guidelines of the new Purchasing Act. In particular this advocates a fair interaction with the new law and a discussion free from prejudice. The reform is also evaluated within the context of European Civil Rights Standardisation.